Procesy kontaktního poškození ložiskových materiálů - Chaloupka, Petr (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Obsahem této bakalářské práce je pojednání o procesech kontaktního poškození ložisek a jejich materiálů, rozbor jednotlivých druhů degradace materiálu, kontaktní únavová pevnost a způsoby jejího měření. Závěrem práce jsou rozebrány směry budoucího vývoje v optimalizaci ložisek.

The focus of this bachelor’s thesis is treatise on processes of contact failures of bearings and theirs materials analyse type of degradation processes of material, contact fatigue strength and means of metering. In fine of bachelor’s thesis are given development of future tendencies in optimalization of bearings.
Processes of contact damage bearing materials
Keywords: Ložisko; materiály ložisek; degradační procesy; kontaktní únava; únavová pevnost; pitting; opotřebení.; Bearing; materials of bearing; degradation processes; contact fatigue; fatigue strength; pitting; wear.